2016
DOI: 10.1111/mmi.13304
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐sensitivity of σH and Spo0A prevents sporulation of Bacillus subtilis at high osmolarity avoiding death during cellular differentiation

Abstract: Summary The spore-forming bacterium Bacillus subtilis frequently experiences high osmolarity as a result of desiccation in the soil. The formation of a highly desiccation-resistant endospore might serve as a logical osmostress escape route when vegetative growth is no longer possible. However, sporulation efficiency drastically decreases concomitant with an increase in the external salinity. Fluorescence microscopy of sporulation-specific promoter fusions to gfp revealed that high salinity blocks entry into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 101 publications
4
21
0
Order By: Relevance
“…However, the portion of differential expression within the σ E , σ F , σ G , and σ K regulons was relatively low and can be explained by very low expression levels, non-sporulation-related gene functions, and/or different degradation rate of dormant spore transcripts in stressed vs. non-stressed outgrowing spores (Dataset S1 ). All differentially expressed σ H -genes except the σ W -dependent spo0M were downregulated (Table 3 ), consistent with the role of σ H in sporulation initiation that is blocked at high salinity (Ruzal et al, 1998 ; Widderich et al, 2016 ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…However, the portion of differential expression within the σ E , σ F , σ G , and σ K regulons was relatively low and can be explained by very low expression levels, non-sporulation-related gene functions, and/or different degradation rate of dormant spore transcripts in stressed vs. non-stressed outgrowing spores (Dataset S1 ). All differentially expressed σ H -genes except the σ W -dependent spo0M were downregulated (Table 3 ), consistent with the role of σ H in sporulation initiation that is blocked at high salinity (Ruzal et al, 1998 ; Widderich et al, 2016 ).…”
Section: Resultssupporting
confidence: 75%
“…In its natural habitats, B. subtilis is frequently exposed to increases in environmental salinity, which has profound influences on cellular physiology and triggers adaptive responses (Bremer, 2002 ; Hoffmann and Bremer, 2016 ). High salinity exerts detrimental effects on B. subtilis spore formation (Ruzal et al, 1998 ; Widderich et al, 2016 ), spore germination (Nagler et al, 2014 , 2015 , 2016 ; Nagler and Moeller, 2015 ), and, as shown here and previously, spore outgrowth (Tovar-Rojo et al, 2003 ; Nagler et al, 2014 , 2016 ). Although it seems counter-intuitive that high salinity inhibits the formation of desiccation resistant spores, blocking this costly cellular differentiation program most likely reflects the inability of starving cells to gather sufficient resources (e.g., for the massive production of osmoprotective proline) required for sporulation during simultaneous salt stress (Brill et al, 2011a ; Widderich et al, 2016 ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The Göttingen Genomics Laboratory (Göttingen, Germany) performed library preparation and sequencing on Illumina instruments. The reads were mapped on the B. subtilis and E. coli reference genomes NC_000964 and U00096, respectively, from GenBank (Blattner et al, 1997;Barbe et al, 2009) as previously described (Widderich et al, 2016) using the Geneious software package (Biomatters) (Kearse et al, 2012). All identified mutations were verified by performing PCRs and Sanger sequencing.…”
Section: Genome Sequencingmentioning
confidence: 99%
“…Previous studies of salt‐adapted B. subtilis cells had revealed alterations in gene expression that affect multiple aspects of cellular physiology, namely uptake and synthesis of osmoprotectants (Kappes et al ., 1996; von Blohn et al ., 1997; Kappes et al ., 1999; Brill et al ., 2011; Hoffmann et al ., 2013), cell wall metabolism and cell division (Dartois et al ., 1998; Steil et al ., 2003; Fischer and Bremer, 2012), iron metabolism (Hoffmann et al ., 2002; Steil et al ., 2003), degradative enzyme synthesis (Kunst and Rapoport, 1995), endospore formation (Kunst and Rapoport, 1995; Ruzal et al ., 1998; Widderich et al ., 2016) and motility (Steil et al ., 2003). In one of these studies global gene expression profiling of high‐salinity adaptation of B. subtilis was performed using a first generation DNA array with PCR products spotted on a nylon membrane (Steil et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%